Professional education: students' experience in an aquaculture extension project in the Marajó archipelago, Amazon, Brazil (Research, Society and Development, 2020)
The technical and rural extension assistance is considered one of the branches of aquaculture that is shaped by educational processes. Thus, the objective of the research was to analyze the contribution of the extension project in aquaculture in the professional formation of students in the Marajó archipelago (Pará, Brazil). The project "Study of the profile of fish farming in the municipality of Breves/Pará as a rural extension practice in the Amazon marajoara" was executed by the Instituto Federal de Educação, Ciência e Tecnologia do Pará (IFPA) Campus Breves. The project’s duration was from October 2016 to April 2017. At the end, interviews were conducted with students from the Technical in Agriculture and Initial and Continuing Training courses in Fish Breeding in Excavated Nurseries, participants in extensionist practices. The results showed that extension activities in aquaculture are relevant and significant for the construction of knowledge, and that they will substantiate and support the professional practice of these students in a concrete and effective way. It is emphasized that the extension project is an excellent channel of teaching-learning, because it brought a series of mutual benefits among the actors (students and fish farmer) involved in the teaching of aquaculture.